Design and Fabrication of Rectifying Antenna Circuit for Wireless Power Transmission System Operating At ISM Band - Chuc Huu Doan; Duong Gia Bach (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper introduces an overview of a rectifying antenna (rectenna) circuit topology for microwave power transmission system. Specially, a rectenna based on a microstrip patch antenna and a microwave double voltage rectifier at 2.45GHz were designed and fabricated.  The antenna’s return loss is achieved of -15 dB at 2.45GHz. The microwave to DC conversion efficiency of the rectenna was measured as 71.5% with 22 dBm input power and 810 Ohm load. The design  and simulated results  were  carried out  by  the  microwave engineering professional  design software,  known as ADS2009 package. All design and simulation results will be reported.